2006
DOI: 10.1021/bi0522394
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Characterization of Escherichia coli TadA, the Wobble-Specific tRNA Deaminase

Abstract: The essential tRNA-specific adenosine deaminase catalyzes the deamination of adenosine to inosine at the wobble position of tRNAs. This modification allows for a single tRNA species to recognize multiple synonymous codons containing A, C, or U in the last (3'-most) position and ensures that all sense codons are appropriately decoded. We report the first combined structural and kinetic characterization of a wobble-specific deaminase. The structure of the Escherichia coli enzyme clearly defines the dimer interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 33 publications
3
83
0
Order By: Relevance
“…A similar K M value of 0.72 +/À 0.11 mM was observed for the partially purified (600-fold pure) native enzyme, suggesting that our recombinant enzyme is a fair representation of that natively expressed in T. brucei (data not shown). The observed K M is also within the range of the E. coli ADATa enzyme (K M = 0.83 mM) (Kim et al 2006). However, the E. coli enzyme shows a 10-fold better k cat (Kim et al 2006).…”
Section: The C Terminus Of Tbadat2 Is Crucial For Enzyme Activitysupporting
confidence: 62%
See 1 more Smart Citation
“…A similar K M value of 0.72 +/À 0.11 mM was observed for the partially purified (600-fold pure) native enzyme, suggesting that our recombinant enzyme is a fair representation of that natively expressed in T. brucei (data not shown). The observed K M is also within the range of the E. coli ADATa enzyme (K M = 0.83 mM) (Kim et al 2006). However, the E. coli enzyme shows a 10-fold better k cat (Kim et al 2006).…”
Section: The C Terminus Of Tbadat2 Is Crucial For Enzyme Activitysupporting
confidence: 62%
“…The observed K M is also within the range of the E. coli ADATa enzyme (K M = 0.83 mM) (Kim et al 2006). However, the E. coli enzyme shows a 10-fold better k cat (Kim et al 2006). The ADAT2 C-terD5 had a K M of 0.76 +/À 0.21 mM and a k cat of 0.14 +/À 0.05 min À1 (Table 2 ; Fig.…”
Section: The C Terminus Of Tbadat2 Is Crucial For Enzyme Activitysupporting
confidence: 62%
“…Again there are two viable possibilities. One possibility would be that Zn 2ϩ coordination is still standard, as in the case of bacterial ADATa (13)(14)(15)18), where each subunit binds one Zn 2ϩ ( Fig. 5A and supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…34 is generated by bacterial homodimeric ADATa with each monomer coordinating one Zn 2ϩ and containing all the additional amino acids needed for catalysis (13)(14)(15). Inosine has not been described in mitochondria, but a recent report showed that a bacteria-type ADATa enzyme plays key functions in inosine formation and thus translation in chloroplasts (16,17).…”
mentioning
confidence: 99%
“…This enzyme destabilizes double-stranded RNA through conversion of adenosine to inosine (10). Likewise, ADAT is a tRNA-specific ADA, changing tRNA to allow for a wobble base pairing (11). The total plasma ADA can be determined by measurement of the ammonia liberated from adenosine.…”
mentioning
confidence: 99%